Black women’s ‘two-ness’ in african-american literature: can black and white worlds join together? - DOI: 10.4025/actascilangcult.v32i1.4767 - Martins, José Endoença (Acta Scientiarum. Language and Culture, 2009)
The article discusses how black women keep contacts with both black and white worlds in novels written by African-American female writers. In Toni Morrison’s (1970) The Bluest Eye, Pecola Breedlove keeps contact with the white world through her assimilationist behavior; in Alice Walker’s (1982) The Color Purple, Celie freezes herself in the black world by playing the role of the nationalist Negro; finally, in Lorraine Hansberry’s (1987) A Raisin in the Sun, Mama Younger joins black and white worlds together when she develops a catalyst agenda, as she moves to a white neighborhood.